Edukasi Stunting bagi Masyarakat Desa Sawitto Bungin Enrekang - Galib, Andi Ahmad Chabir; Elihami, Elihami; Ismaya, Ismaya; Cahyani, Cahyani; Hairul, Muh; Hendriadi, Hendriadi; Agustiana, Ria; Saputri, Fira (LP2M Universitas Muhammadiyah Enrekang, 2023)
Stunting or failure to thrive in toddlers due to chronic malnutrition, is a serious problem in Indonesia. To overcome stunting, increasing public awareness about the negative impact of stunting on children through stunting education seminars is one effective approach. The stunting education seminar shows that this activity is able to increase public knowledge and awareness about stunting, especially among young women, female students, pregnant women and the general public. Through this activity, the public can understand the importance of balanced nutrition and a healthy lifestyle in preventing stunting in children. Apart from that, stunting education seminar activities can also help increase community participation in stunting prevention. Thus, stunting education seminar activities are an effective step in increasing public awareness of the negative impacts of stunting on children and efforts to prevent stunting.